Informational sources of sport tourists attending ISTAF super series - Zarei, Azadeh; Yusof, Aminuddin (University of Pitesti, Romania, 2014)
Efforts at organizing sport event should involve developing marketing communications that feature sport-events information to potential sport tourists. Using a human and a marker component of Tourist Attraction System Model by Leiper (1990), this paper explores that sport tourists vary in some extent which they choose event informational sources to the commencement of traveling decisions related attending Sepaktakraw event. The respondents included 316 sport tourists in two categories of domestic sport tourists (n=224) and foreign sport tourists (n=92) attending ISTAF Super Series. Differences were found. Findings show that a great number of domestic sport tourists reported using generating markers related mass communication items, while social networking was the most important sources of information to foreign sport tourists. This research provides different strategic use of event informational sources for sport event marketers and organizers to enhance sport tourists’ behavioral motives for great attendance.